An Inclusive Performance Analysis of Single-branch Single-relay AF Transmission in a Mixed Rayleigh-Nakagami-m Fading Environment - Slimane Benmahmoud (Journal of Telecommunications and Information Technology, 2019)
In this paper, the end-to-end performance of a single-branch two-hop amplify-and-forward (AF) relaying network in a mixed Rayleigh-Nakagami-m fading environment, is investigated. Four diﬀerent fading scenarios and three standard relay conﬁgurations for each scenario are considered. Exact analytical expressions for the outage probability and tight upper bounds for the ergodic capacity are derived. Results of Monte Carlo simulations are provided to verify the accuracy of the analytical results.